2020
DOI: 10.1038/s41598-020-75128-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel genomic targets of valosin-containing protein in protecting pathological cardiac hypertrophy

Abstract: Pressure overload-induced cardiac hypertrophy, such as that caused by hypertension, is a key risk factor for heart failure. However, the underlying molecular mechanisms remain largely unknown. We previously reported that the valosin-containing protein (VCP), an ATPase-associated protein newly identified in the heart, acts as a significant mediator of cardiac protection against pressure overload-induced pathological cardiac hypertrophy. Still, the underlying molecular basis for the protection is unclear. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 47 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…SORBS1 encodes a CasitasB.1ineagelymphoma (CBL)–associated protein that functions in the signaling and stimulation of insulin, and it also been confirmed to be related to COPD. 81–83 Studies have found that SORBS1 can participate in immune-related gene signal transduction, and its increased expression is closely related to poor prognosis in cervical cancer, 84 gastric cancer, 85 prostate cancer, 86 and colorectal cancer. 87 However, the exact role and diagnostic significance of SORBS1 in BRCA are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…SORBS1 encodes a CasitasB.1ineagelymphoma (CBL)–associated protein that functions in the signaling and stimulation of insulin, and it also been confirmed to be related to COPD. 81–83 Studies have found that SORBS1 can participate in immune-related gene signal transduction, and its increased expression is closely related to poor prognosis in cervical cancer, 84 gastric cancer, 85 prostate cancer, 86 and colorectal cancer. 87 However, the exact role and diagnostic significance of SORBS1 in BRCA are not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies demonstrated a strong link between the down-regulation of VCP expression and cardiomyocyte hypertrophy and heart failure under pressure-overload stress [ 15 , 18 ]. We also showed that overexpression of VCP protects the heart against cardiac injuries and prevents cardiac deterioration under various stress conditions [ 15 , 16 , 18 , 19 , 20 , 21 ]. These results indicate that VCP is a crucial protector in the stressed heart.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that VCP was decreased in the hypertensive rat hearts and acts as a driving force for the cardiac pathogenesis caused by pressure overload [ 15 ]. Reciprocally, cardiac-specific overexpressing VCP protects mouse hearts against pressure-overload-induced pathological hypertrophy [ 15 , 16 , 17 ] and heart failure [ 18 ], and it also protects against stress-induced cardiomyocyte death in vitro and reduced ischemic injury in vivo [ 19 , 20 , 21 ]. These results together indicated that VCP plays a critical protective role in the heart under stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The genes we used for prognostic classifier constructing were SORBS1 and SDC1. SORBS1 encodes a CasitasB.1ineagelymphoma (CBL)-associated protein that functions in the signaling and stimulation of insulin, and it also been confirmed to be related to COPD [80][81][82] . Studies have found that SORBS1 can participate in immune-related gene signal transduction, and its increased expression is closely related to poor prognosis in cervical cancer 83 , gastric cancer 84 , prostate cancer 85 , and colorectal cancer 86 .…”
Section: Prognostic Gene-drug Interaction Network Analysismentioning
confidence: 99%